The Effects of Internal Control Systems on Cooperative's Profi tability: A Case of Koperasi ABC Berhad - Shabri, Shafawaty Mohamad; Saad, Ram Al Jaffri; Bakar, Azizi Abu (International Review of Management and Marketing, 2016)
This study investigates the effect of internal control systems on cooperative profitability. Internal control is described by Committee of Sponsoring Organizations of the Treadway Commission (COSO) Framework, which is limited to Control Environment, Risk Assessment, Control Activities, Information and Communication, and Monitoring. This study was conducted using a qualitative approach, where a case study method was applied. Data were collected through interview sessions and documentary evidences. From the findings of study, it was concluded that the internal control systems applied in Koperasi ABC Berhad can be considered effective and satisfactory. This was based on the implementation of all components of internal control systems, as described by the COSO Framework within the cooperative. However, financial losses occurred in the cooperative, caused by inefficient cost control and not due to weak internal controls. Profitability can be improved with a new development plan as well as implementation of effective internal control systems within the cooperative. Good or strong internal control systems would have an effect on the cooperative's profitability as well as help the stability and growth of the cooperative movement in Malaysia. Keywords: Internal Control Systems, Cooperatives, Profitability. JEL Classifications: H10, B51